Beneficial response to mycophenolate mofetil by patients with autoimmune hepatitis who have failed standard therapy, is predicted by older age and lower immunoglobulin G and INR levels. Issue 10 (11th April 2019) - Nicoll, Amanda J.; Roberts, Stuart K.; Lim, Ricky; Mitchell, Joanne; Weltman, Martin; George, Jacob; Wigg, Alan; Stuart, Katherine; Gow, Paul; MacQuillan, Gerry; Tse, Edmund; Levy, Miriam; et al.
Summary: Background: Mycophenolate mofetil is a commonly used salvage therapy for patients with autoimmune hepatitis (AIH). Aim: To evaluate the predictors of response to mycophenolate rescue therapy to facilitate clinical decision making. Methods: We performed a retrospective observational cohort study of AIH patients managed in 17 major Australian liver centres who received mycophenolate after an inadequate response or intolerance to corticosteroids with/without thiopurine(s). Baseline demographic, clinical and laboratory variables were compared between responders and nonresponders. A multivariable logistic regression model was developed using forward selection to identify independent predictors of treatment response. Results: A total of 105 patients received mycophenolate rescue therapy of whom 63 (60%) achieved biochemical remission. On univariable analysis, older age ( P = 0.003), INR < 1.1 ( P = 0.02), and lower immunoglobulin gamma (IgG; P < 0.002) levels were associated with treatment response, while no association was found with cirrhosis status ( P = 0.07) or treatment indication ( P = 0.63). On multivariable analysis, lower pre‐treatment serum IgG level ( P = 0.01), higher age at commencing mycophenolate ( P = 0.01) and higher INR ( P = 0.03) were the only significant independent predictors. An IgG level <17 g/L had a positive and negative predictive value for response of 71% and 60% respectively, while age ≥54 years when commencing mycophenolate had a positive and negative predictive value for response of 80% and 59% respectively. Conclusion: Mycophenolate remains an excellent treatment option for patients with AIH refractory to or intolerant of standard therapy with those most likely to benefit being older and/or having lower pre‐treatment IgG levels.